Effect of Mobile Phase pH on the Electrospray Ionization Efficiency and Qualitative Analysis of Pharmaceuticals in ESI + LC-MS/MS - Kafeenah, Husam I.S.; Osman, Rozita; Bakar, Nor Kartini Abu (Oxford University Press, 2019)
The effect of mobile phase pH on positive ionization process and retention time of nine pharmaceuticals on ultra-performance liquid chromatography-electrospray-tandem mass spectrometry (LC-MS/MS) was discussed. The effective use of high and low mobile phase pH in LC-MS/MS qualitative analyses method was also evaluated by comparing the instrument detection limit, quantification limit, precision, linearity and signal to noise (S/N) under low and high mobile phase pH. In this work, six mobile phase pH that ranged between pH 2 and pH 10 were used to evaluate the effect of the mobile phase pH changes on the ionization process in electrospray ionization. Results revealed that high mobile phase pH ionized more pharmaceuticals molecules and gave a higher signal than low mobile phase pH in positive ionization mode. The results proved that ammonium ion was better as a proton donor in high pH mobile phase than the hydronium ion in acidic mobile phase. The results revealed that the qualitative LC-MS/MS analyses method by using high mobile phase pH has better performance for most analytes in terms of sensitivity, precision, linearity and S/N than the low mobile phase pH. © 2019 The Author(s). Published by Oxford University Press. All rights reserved.